Apoyo en supervisión y control de obra en el desarrollo de proyectos de la Constructora M S N Limitada en Boyacá (2023)
The degree project is carried out through the internship modality which is carried out in the private company CONSTRUCTORA M S N LIMITADA of Duitama, Boyacá, the company within the activities it develops has a concrete production plant, where it offers the supply of concrete in municipalities such as Sogamoso, Paipa, Duitama, Santa Rosa de Viterbo, Cerinza and Belén, through direct unloading or with the concrete pump service depending on the need. For the development of the internship, support was provided in technical activities such as carrying out visits to calculate the volume of concrete necessary for the supply, in addition to the visual inspection of the entrance of the equipment to the work, verifying the access routes and the way in which the anchoring and location of the vehicles for the unloading of the concrete were carried out and the support was provided in the supervision of the pouring of concrete in order to guarantee good disposition on site and give recommendations on its correct curing to guarantee the design resistance.